Supermassive black holes and their feedback effects in the IllustrisTNG simulation - Weinberger, Rainer; Springel, Volker; Pakmor, Rüdiger; Pillepich, Annalisa (Monthly notices of the Royal Astronomical Society, 2018)
ABSTRACT. We study the population of supermassive black holes (SMBHs) and their effects on massive central galaxies in the IllustrisTNG cosmological hydrodynam
Gesehen am 01.02.2019